2007
DOI: 10.1152/ajplung.00262.2006
|View full text |Cite
|
Sign up to set email alerts
|

Altered cholesterol homeostasis in cultured and in vivo models of cystic fibrosis

Abstract: White NM, Jiang D, Burgess JD, Bederman IR, Previs SF, Kelley TJ. Altered cholesterol homeostasis in cultured and in vivo models of cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
100
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 44 publications
(58 reference statements)
13
100
1
Order By: Relevance
“…Respiratory inflammation and increased expression of cytokines have been reported to increase in mice lacking functional lysosomal acid lipase, or following administration of a cholesterol-rich diet (11,12,62,63). Conversely, recent studies suggest a protective role of the cholesterol-lowering drugs statins in smoke-driven respiratory inflammation, COPD, and asthma in both mice (64 -67) and humans (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory inflammation and increased expression of cytokines have been reported to increase in mice lacking functional lysosomal acid lipase, or following administration of a cholesterol-rich diet (11,12,62,63). Conversely, recent studies suggest a protective role of the cholesterol-lowering drugs statins in smoke-driven respiratory inflammation, COPD, and asthma in both mice (64 -67) and humans (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol synthesis measurements were performed as described ( 11 ). Briefl y, mice and the matched controls were given an intraperitoneal injection ( ‫ف‬ 24 µl per g body weight) of deuterated saline (9 g NaCl in 1,000 ml of 99% 2 H 2 O; Sigma-Aldrich, St. Louis, MO).…”
Section: Measuring Cholesterol Synthesis In Vivomentioning
confidence: 99%
“…There are three different manifestations of the CF cholesterol phenotype: perinuclear free-cholesterol accumulation, increased membrane cholesterol content, and increased de novo cholesterol synthesis ( 10,11 ). Previously we demonstrated that accumulated perinuclear cholesterol in CF-cell models is reversible in the presence of the cAMP binding competitor Rp -cAMPS, and it colocalizes with internalized ␤ 2-adrenergic receptor ( ␤ 2-AR) ( 12 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In these patients, altered fatty acid levels including reduced levels of docosahexaenoic acid [28] have been described and docosahexaenoic acid supplementation improved the clinical status in some studies [29] . Other lipid anomalies in cystic fibrosis are altered cholesterol homeostasis [30] , and elevated cholesteryl ester concentrations in tracheobronchial secretions [31] . We have found an increased cholesteryl ester representation in the lipid content of bronchoalveolar lavages obtained from pediatric cystic fibrosis patients [32] .…”
Section: Airwaysmentioning
confidence: 99%